Faktor-Faktor yang Memengaruhi Permintaan Buah Jeruk Siam di Kota Surakarta - Devanie Anggun Putri Leksana; Mohamad Harisudin; Refa'ul Khairiyakh (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Increasing public awareness of the importance of fulfilling nutrition and vitamins has resulted in people consuming fruit more massively. One popular fruit is siam citrus because it tends to taste sweet and is readily available on the market, including in Surakarta City. Surakarta City is a potential market for siam citrus because the public consumption of the fruit increases yearly. In contrast, public consumption of siam citrus fluctuates from year to year. The fluctuating level of public consumption means that the demand for siam citrus is also uncertain. Considering this, it is imperative to understand the variables influencing Surakarta City's demand for siam citrus. One hundred respondents who purchased siam citrus from